(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Chuvasova N. O. Development of operational component of cognitive activity of students of higher pedagogical institutions. The article revealed the structure of the operational component of the cognitive activity of future teachers in higher education and the ways and methods of solution of the operational component of cognitive activity.